Potential of Citizen Science for Enhancing Infrastructure Monitoring Data and Decision‐Support Models for Local Communities. Issue 7 (4th January 2019) - Gharaibeh, Nasir; Oti, Isaac; Meyer, Michelle; Hendricks, Marccus; Van Zandt, Shannon
Abstract: Citizen science is a process by which volunteer members of the public, who commonly lack advanced training in science, engage in scientific activities (e.g., data collection) that might otherwise be beyond the reach of professional researchers or practitioners. The purpose of this article is to discuss how citizen‐science projects coordinated by interdisciplinary teams of engineers and social scientists can potentially enhance infrastructure monitoring data and decision‐support models for local communities. The article provides an interdisciplinary definition of infrastructure data quality that extends beyond accuracy to include currency, timeliness, completeness, and equitability. We argue that with this expanded definition of data quality, citizen science can be a viable method for enhancing the quality of infrastructure monitoring data, and ultimately the credibility of risk analysis and decision‐support models that use these data. The article concludes with a set of questions to aid in producing high‐quality infrastructure monitoring data by volunteer citizen scientists.